Model Teoritis Penyesuaian Kurikulum Bagi Anak Berkebutuhan Khusus - Deny Ari Yardi; Rafhika Wulandari; Susan Apriani; Opi Andriani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The aim of this research is to determine the theoretical model of curriculum for children with special needs.  This type of research is qualitative in nature with data collection mainly through books and journals as data sources.  The data analysis technique is to use data triangulation.  The research objects are books and journals about children with special needs.  The research results concluded that the theoretical model in adapting the curriculum for children with special needs is quite good because the teaching models used are the regular education model, the open education/natural school model, as well as the home education service model in inclusive education.